2021
DOI: 10.48550/arxiv.2108.07255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray spectra, light-curves and SEDs of blazars frequently observed by Swift

P. Giommi,
M. Perri,
M. Capalbi
et al.

Abstract: Blazars research is one of the hot topics of contemporary extragalactic astrophysics. That is because these sources are the most abundant type of extragalactic ๐›พ-ray sources and are suspected to play a central role in multi-messenger astrophysics. We have used swift_xrtproc, a tool to carry out an accurate spectral and photometric analysis of the Swift-XRT data of all blazars observed by Swift at least 50 times between December 2004 and the end of 2020. We present a database of X-ray spectra, best-fit paramet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…On the other hand, during the second flare the linear-Pearson test resulted in 0.44 clearly showing a softer-when-brighter trend. Such a pattern was also observed in the X-ray emission of OJ 287 (e.g., Kapanadze et al 2018;Prince et al 2021;Giommi et al 2021). During this flare, the spectral index of 2.56 ยฑ 0.03 was the softest ever observed, very different from the values normally observed in BL Lac (typically ฮ“ X โ‰ค 2.0).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On the other hand, during the second flare the linear-Pearson test resulted in 0.44 clearly showing a softer-when-brighter trend. Such a pattern was also observed in the X-ray emission of OJ 287 (e.g., Kapanadze et al 2018;Prince et al 2021;Giommi et al 2021). During this flare, the spectral index of 2.56 ยฑ 0.03 was the softest ever observed, very different from the values normally observed in BL Lac (typically ฮ“ X โ‰ค 2.0).…”
Section: Discussionsupporting
confidence: 57%
“…During the considered period, the Swift satellite (Gehrels et al 2004) observed BL Lac 610 times with single exposures ranging from 1.13 to 16.46 ks. All the data were downloaded and processed using Swift_xrtproc automatic tool for XRT data analysis developed within the Open Universe Initiative (Giommi et al 2021). This tool automatically downloads the raw data and processes it using the XRT-PIPELINE task adopting standard parameters and filtering criteria.…”
Section: Swift Xrtmentioning
confidence: 99%
“…To search for X-ray variability we use the 1 keV X-ray light curves as obtained by Giommi et al (2021). The Swift/XRT data products are based on the pipeline, the procedure, and methodology developed for the Open Universe for Blazars project (Giommi et al 2018(Giommi et al , 2019.…”
Section: X-ray Light Curvesmentioning
confidence: 99%
“…The Swift/XRT data products are based on the pipeline, the procedure, and methodology developed for the Open Universe for Blazars project (Giommi et al 2018(Giommi et al , 2019. Here, we provide a brief outline of the analysis procedure, but for a comprehensive description we refer the reader to Giommi et al (2021). Xray source and background events were extracted from XRT data.…”
Section: X-ray Light Curvesmentioning
confidence: 99%
See 1 more Smart Citation